Analysis of Biology Education Students' Learning Outcomes in Environmental Biology Practicum Plankton Identification Material - Aryani, Ima; Utami, Dian Putri (Universitas Muhammadiyah Surakarta, 2024)
Practicum is an activity that supports students to interact directly with real material. One of the practical activities is observing objects so they are easy to learn. This research aims to determine the implementation of environmental biology practicum materials on plankton identification for biology education students at Muhammadiyah University of Surakarta. This type of research is descriptive qualitative. The sample for this research was 42 first semester students at the Biology Education Study Program, Faculty of Teacher Training and Education, Muhammadiyah University of Surakarta. Data collection techniques for cognitive learning outcomes were carried out using pretest and posttest, as well as observation questionnaires regarding student activities in practice as a result of psychomotor learning. Data analysis uses descriptive statistics. The research results show that cognitive learning outcomes seen from the average test results have differences, namely, the pretest average is 58.5 and the posttest average is 86.3. Psychomotor learning results were 78.8 with good criteria.